Numerical analysis on the performance of a radiant cooling panel with serpentine-based design - Radzai M.H.M.; Yaw C.T.; Lim C.W.; Koh S.P.; Ahmad N.A. (MDPI AG, 2023)
Air conditioning; Air quality; Computational fluid dynamics; Condensation; Cooling systems; Drops; Energy conservation; Indoor air pollution; Pressure drop; Serpentine; Water pipelines; Condensation problems; Cooling performance; Dewpoint temperature; Energy saving potential; Flow configurations; Operating condition; Risk of condensation; Supply water temperature; Cooling